2017
DOI: 10.1186/s13287-017-0739-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low-intensity pulsed ultrasound (LIPUS)-pretreated human amnion-derived mesenchymal stem cell (hAD-MSC) transplantation on primary ovarian insufficiency in rats

Abstract: BackgroundHuman amnion-derived mesenchymal stem cells (hAD-MSCs) have the features of mesenchymal stem cells (MSCs). Low-intensity pulsed ultrasound (LIPUS) can promote the expression of various growth factors and anti-inflammatory molecules that are necessary to keep the follicle growing and to reduce granulosa cell (GC) apoptosis in the ovary. This study aims to explore the effects of LIPUS-pretreated hAD-MSC transplantation on chemotherapy-induced primary ovarian insufficiency (POI) in rats.MethodsThe anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 65 publications
5
55
0
Order By: Relevance
“…Scientists recently reported that stem cell transplantation improves ovarian function by increasing the expression of related hormones and by preventing GC apoptosis, which suggests a therapeutic potential [30]. As shown in Table 1, the therapeutic effects of stem cells can be measured by several factors, such as folliculogenesis, the GC apoptosis rate, vascular formation, the pregnancy rate and the regulation of hormone levels (Table 1) [42].…”
Section: Potential Therapeutic Effectsmentioning
confidence: 99%
“…Scientists recently reported that stem cell transplantation improves ovarian function by increasing the expression of related hormones and by preventing GC apoptosis, which suggests a therapeutic potential [30]. As shown in Table 1, the therapeutic effects of stem cells can be measured by several factors, such as folliculogenesis, the GC apoptosis rate, vascular formation, the pregnancy rate and the regulation of hormone levels (Table 1) [42].…”
Section: Potential Therapeutic Effectsmentioning
confidence: 99%
“…Indeed, in a study using low-intensity pulsed ultrasound (LIPUS)-pretreated AD-MSCs, the expression of several growth factors, including IGF1, FGF2, and VEGF, reduced the expression of IL-1β, IL-6, and TNF-α in the ovaries of POF rats. Interestingly, LIPUS pretreatment with AD-MSC transplantation was more effective in decreasing chemotherap yinduced inflammation and apoptosis in the ovarian tissue of POF rats(122). Another study examined the levels of monocyte chemotactic protein-1 (MCP-1), one of the key chemokines in normal and preeclamptic pregnancies, but observed no significant difference in its expression in AD-MSCs(123).…”
mentioning
confidence: 99%
“…In the combined treatment, the effects of ultrasound on cells before and after the transplantation of AdMSCs at the cavitation threshold mechanical index of the culture medium and skin tissue were studied for delaying and preventing radiation damage. In a similar study, Ling et al 12 investigated the effect of ultrasound radiation at a frequency of 0.25 MHz and an intensity of 30 mW/cm 2 on AdMSCs before transplantation. After 5 days of ultrasonic irradiation for 30 min, the cells were injected through the tail vein of a mouse which had ovarian failure due to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Low-intensity ultrasound is a special type of energy that results in the transmission of acoustic pressure and mechanical stress. The main idea behind the use of low-intensity ultrasound in the medical field is the reconstruction of radiation injuries as a non-ionization method 12 .…”
Section: Introductionmentioning
confidence: 99%